IMPLEMENTASI MODEL PEMBELAJARAN ROLE PLAYING TERHADAP PENINGKATAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA SD - Mangopo, Melki; Abdul Malik Iskandar; Satriawti; Alfiani Damayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Implementation of the Role Playing learning model to increase learning motivation in Pancasila education learning in elementary schools guided by Abdul Malik Iskandar and Satriawati. This study aims to describe the implementation of the Role Playing learning model and its impact on increasing student learning motivation in the Pancasila Education subject. This study is a Classroom Action Research (CAR) study using a Quantitative approach. This study took place at Bawakaraeng I Elementary School, Makassar City. The sampling technique used simple random sampling by selecting class IV C with a total sample of 21 The data collection technique in this study used a questionnaire related to the characteristics of an object to be studied. The questionnaire presents a set of questions or statements to be answered as a benchmark. The results of the frequency distribution of learning motivation in cycle I are in the interval 56-70 or in the sufficient category with a frequency of 10 students, interval 71-85 or in the good category. with a frequency of 11 students, then the results of the frequency distribution of learning motivation in Cycle II are in the interval 56-70 or in the sufficient category with a frequency of 1 student, interval 71-85 or good category with a frequency of 18 students and interval 86-100 or very good category with a frequency of 2 students. The results of the study indicate that the implementation of the role playing model can increase student learning motivation, both in terms of activeness, curiosity, enthusiasm, and responsibility for learning. This increase can be seen from the comparison of data between cycles I and II. Thus, the role playing model has proven effective in creating an interesting, meaningful, and enthusiastic Pancasila Education learning atmosphere for students.